Percutaneous left atrial appendage occlusion for stroke prevention in atrial fibrillation: an update. Issue 1 (7th June 2014) - De Backer, O; Arnous, S; Ihlemann, N; Vejlstrup, N; Jørgensen, E; Pehrson, S; Krieger, T D W; Meier, P; Søndergaard, L; Franzen, O W
Abstract : Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia encountered in clinical practice. One of its most devastating complications is the development of thromboembolism leading to fatal or disabling stroke. Oral anticoagulation (OAC, warfarin) is the standard treatment for stroke prevention in patients with AF with an increased stroke risk. However, there are several obstacles to long-term OAC therapy, including the risk of serious bleeding, several drug–drug interactions and the need for frequent blood testing. Although newer oral anticoagulants have been developed, these drugs also face issues of major bleeding and non-compliance. Therefore, alternative treatment options for stroke prevention in patients with AF with a high stroke risk are needed. Percutaneous left atrial appendage (LAA) occlusion is an evolving therapy, which should be taken into consideration in those patients with non-valvular AF with a high stroke risk and contraindications for OAC. This article aims to discuss the rationale for LAA closure, the available LAA occlusion devices and their clinical evidence until now. Moreover, we discuss the importance of proper patient selection, the role of various imaging techniques and the need for a more tailored postprocedural antithrombotic therapy.